Republic of Serbia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2006)
This note compares patterns of domestic investment in Serbia with those in other central and eastern European countries, noting the relationships with external balances. The structure of participation and employment rates suggests a need for analysis of the impact of labor market institutions on youth and women. A further focus on redeployment services would be appropriate. The Serbian banking system, the implications of the structure of Serbia's economy, the operational framework of monetary policy, and the adoption of an inflation targeting regime have been discussed.